Karl Jay Shapiro papers - Shapiro, Karl Jay, 1913-2000.; Shapiro, Karl Jay, 1913-2000.; Shapiro, Karl Jay, 1913-2000.
Drafts, typescripts, proofs, and printed copies of Shapiro's published and unpublished articles, essays, lectures, and writings relating chiefly to the nature of poetry and its place in American society. Includes drafts of his books, The Bourgeois Poet (1964) and To Abolish Children and Other Essays (1968).
Poet, editor, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American literature; American poetry; Literature and society -- United States; Poetry; Editors; Educators; Poets